2021
DOI: 10.1007/s40268-021-00352-5
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Pharmacokinetics of HTL0018318, a Novel M1 Receptor Agonist, Given in Combination with Donepezil at Steady State: A Randomized Trial in Healthy Elderly Subjects

Abstract: Introduction HTL0018318 is a selective muscarinic M 1 receptor partial agonist under development for the symptomatic treatment of dementias, including Alzheimer's disease. Clinically, HTL0018318 would likely be used alone or in conjunction with cholinesterase inhibitors (e.g. donepezil). Objective We investigated the safety, tolerability, and pharmacokinetics of HTL0018318 given alone and in combination with donepezil. Methods This was a randomized, double-blind, placebo-controlled trial in 42 (to deliver 36 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Treatment with donepezil and rivastigmine (acetylcholinesterase inhibitors) also resulted in reduced P300 latency and improved cognitive scores in patients with AD [68][69][70][71][72]. A recent randomized trial showed an increase in amplitude of the ERP P300 in patients with cognitive impairment after treatment with HTL0009936 (a selective muscarinic M 1 -acetylcholine receptor agonist) compared to treatment with placebo [73]. Most recently, a double-blind, placebo-controlled phase 1 clinical trial showed a reduction in P300 latency in patients with AD treated with fosgonimeton (a hepatocyte growth factor (HGF)/MET-positive modulator) compared with placebo [74].…”
Section: Erp In Dementiamentioning
confidence: 99%
“…Treatment with donepezil and rivastigmine (acetylcholinesterase inhibitors) also resulted in reduced P300 latency and improved cognitive scores in patients with AD [68][69][70][71][72]. A recent randomized trial showed an increase in amplitude of the ERP P300 in patients with cognitive impairment after treatment with HTL0009936 (a selective muscarinic M 1 -acetylcholine receptor agonist) compared to treatment with placebo [73]. Most recently, a double-blind, placebo-controlled phase 1 clinical trial showed a reduction in P300 latency in patients with AD treated with fosgonimeton (a hepatocyte growth factor (HGF)/MET-positive modulator) compared with placebo [74].…”
Section: Erp In Dementiamentioning
confidence: 99%